Penggunaan Video Sebagai Media Tutorial Pembelajaran terhadap Kemampuan Berceramah Siswa - Agus Riyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the use of video as a learning activity tutorial media on students' speaking abilities. This research uses a quasi experiment method, the technique used in sampling is total sampling technique, the data analysis technique used in this study begins with the analysis prerequisite test that is the distribution of normalitis test, variant homogeneity test and linearity relationship test. The results of the study, obtained Fcount = 19.747 and p = 0,000, average learning outcomes 20.78, the average questionnaire was 60.09. Conclusion, there is an influence of the use of instructional video media on the results of students' lecturing abilities Keywords: Video, Media, Learning, Lecture